P12 Predictors of mood in amyotrophic lateral sclerosis: physical and psychological factors. Issue 10 (7th September 2012) - Martin, N H; Janssen, A; McCrone, P; Lyall, R; Landau, S; Dougherty, A; Sakel, M; Higginson, I; Shaw, C; Al-Chalabi, A; Leigh, P N; Goldstein, L H
Abstract : Objective: This study set out to investigate the relationship between mood and physical and psychological factors in amyotrophic lateral sclerosis (ALS). Method: As part of a longitudinal study investigating decision-making in ALS, 69 ALS patients, recruited from the South East ALS register, were assessed at baseline on measures of mood (Beck Depression Inventory Fast Screen), purpose in life (Purpose in Life Scale) and illness perceptions (Brief Illness Perceptions Questionnaire). Demographic and illness characteristics were also recorded. Hierarchical multiple regression was used to determine the extent to which psychological variables (purpose in life; and illness perceptions—consisting of perceived consequences of illness, personal control, identity, concern and emotions) predicted mood, after accounting for the effects of demographic (age, years of education) and illness characteristics (symptom severity, measured by ALSFRS-R). Results: 42.0% of patients exceeded the recommended clinical cut-off score on the BDI-Fast Screen, suggestive of depression, although most of these (34.8% of the total sample) fell in the mild range. Multiple regression showed that psychological variables (purpose in life and illness perceptions) explained an additional 42% (adjusted R 2 =0.406) of the variance in mood, over and above that explained by demographic and illness characteristics, which only explained a total of 7% of the variance. In the final model, purpose in life was the only statistically significant predictor of mood among ALS patients. Conclusion: Purpose in life, based on the work of Frankl (1959), refers to the degree to which a person experiences a sense of meaning in life and includes, for example, having goals to strive for and relationships to maintain (Hedberg et al, 2011; White, 2004). Frankl (1958) suggested that a lack of purpose in life can weaken the will to confront life situations, producing an "existential vacuum" and resulting in depression and anxiety (Hedberg et al, 2011). Current results suggest that purpose in life may play a more significant role in influencing mood among ALS patients than the beliefs about their illness or the severity of their physical symptoms. Findings, therefore, emphasise the importance of understanding psychological factors leading to risk of mental health problems in this population, and ultimately their relation to prognosis and treatment choices. Funding: This study is funded by the MNDA, UK.